Asian processes and development administration in retrospect [review of] - Bauzon, Kenneth Espana (1975)
A review of Henry S. Albinski (ed.), Asian Political Processes: Essays and Readings (Boston: Allyn and Bacon, Inc., 1971), 426 pp. and Edward W. Weidner (ed.), Development Administration in Asia (Durham, NorLh Carolina: Duke University Press, 1970),
431 pp.
Keywords: Book reviews; Public administration -- Asia